P‐9: High Performance Back Channel Etch Metal Oxide Thin‐film Transistor with Double Active Layers. Issue 1 (May 2016) - Yang, Jong-Heon; Choi, Ji Hun; Pi, Jae-Eun; Kim, Hee-Ok; Park, Eun-Suk; Kwon, Oh-Sang; Nam, Sooji; Cho, Sung Haeng; Yoo, Seunghyup; Hwang, Chi-Sun
Abstract : We fabricated high performance back channel etch (BCE) IZO/AIZTO double‐layer channel oxide thin‐film transistors (TFTs) and analyzed their electrical characteristics and photostability of the devices. The field‐effect mobility of 53.2 cm2/Vs was obtained, and we expect IZO/AIZTO double‐layer BCE TFT can be used as a backplane devices for next generation high performance display applications.